2014
DOI: 10.2754/avb201483s10s103
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll as an indicator of green tea quality

Abstract: The objective of this work was to study the changes in chlorophyll contents in green teas stored under different conditions and to suggest the most suitable way and length of green tea storage. A secondary aim was to evaluate the possibility of using the chlorophyll content as an indicator of tea freshness. Samples for analysis were obtained from a range of tea-growing regions. Chlorophyll contents were measured using UV-vis spectrophotometry. Chlorophyll absorbance was measured at 642.5 and 660 nm. Prior to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
2
15
2
3
Order By: Relevance
“…The total content of chlorophylls was proposed as quality parameter for C. sinensis and the concentration found among 14 samples ranged from 1.18 ± 0.16 to 1.98 ± 0.11 mg/g of sample. [ 48 ] Thus, the value found in the present study was in agreement with the reported value. No report was found about the chlorophyll content in E. uniflora as far as we known.…”
Section: Discussionsupporting
confidence: 93%
“…The total content of chlorophylls was proposed as quality parameter for C. sinensis and the concentration found among 14 samples ranged from 1.18 ± 0.16 to 1.98 ± 0.11 mg/g of sample. [ 48 ] Thus, the value found in the present study was in agreement with the reported value. No report was found about the chlorophyll content in E. uniflora as far as we known.…”
Section: Discussionsupporting
confidence: 93%
“…Pigment and antioxidant contents of food materials No pigment was detected in lotus root, but powdered gardenia seed, green tea, and cactus pear contained chlorophylls and/or carotenoids. Chlorophylls a and b were detected only in green tea powder at 59.46±0.77 and 151.91±7.26 mg/kg, respectively, which were lower than the reported values (11). A wide range of the chlorophyll contents in green tea depending on the cultivating area and processing method has been previously reported (12,13).…”
Section: Resultscontrasting
confidence: 53%
“…The a-value of the color change results agreed with previous research findings that green tea color becomes more reddish as a result of the oxidation of polyphenolic compounds. Chlorophyll is a green pigment in green tea, and its amount decides the final color of green tea infusion [ 23 ]. Light may degrade chlorophyll in RTD green tea infusions during storage because light absorptions of the photosensitizer chlorophyll are at the wavelength of 430 and 660 nm [ 12 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll is a green pigment in green tea, and its amount decides the final color of green tea infusion [ 23 ]. Light may degrade chlorophyll in RTD green tea infusions during storage because light absorptions of the photosensitizer chlorophyll are at the wavelength of 430 and 660 nm [ 12 , 23 ]. Hence, the light may reduce the green color of RTD green tea infusions in the packaging during storage.…”
Section: Resultsmentioning
confidence: 99%